2020
DOI: 10.1080/14992027.2019.1702223
|View full text |Cite
|
Sign up to set email alerts
|

Hearing thresholds and cognitive flexibility in young healthy individuals with normal hearing

Abstract: Objective: Pure tone audiometry may seem to be a relatively easy task for the participant but it may involve cognitive as well as sensory abilities. The aim of this study is to examine the relationship between hearing thresholds in the frequency range 0.125-8 kHz and the core executive function cognitive flexibility in healthy individuals with normal hearing. Design: Experimental study measuring correlations between different pure-tone hearing threshold measures and cognitive flexibility. Pure tone air conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…At the other extreme, the replacement of an earlier misperceived sound with the correct sound when the error later becomes apparent presumably cannot occur without the application of working memory. We also note that even detection of pure tones (i.e., audiometry), which must be the simplest of auditory tasks, is weakly but significantly correlated with cognitive flexibility ( Brännström et al 2020 ).…”
Section: Model Of Speech Understandingmentioning
confidence: 90%
“…At the other extreme, the replacement of an earlier misperceived sound with the correct sound when the error later becomes apparent presumably cannot occur without the application of working memory. We also note that even detection of pure tones (i.e., audiometry), which must be the simplest of auditory tasks, is weakly but significantly correlated with cognitive flexibility ( Brännström et al 2020 ).…”
Section: Model Of Speech Understandingmentioning
confidence: 90%
“…In the present study, we did not evaluate inner ear and cochlear nerve function, such as ABR and OAE, in the control group, so we cannot accurately determine whether this difference was due to differences in the condition of the inner ear and cochlear nerve of the subjects. However, considering the fact that the OAE and ABR in the patient group showed no obvious abnormalities and a previous report that cognitive function affects auditory thresholds (Brännström et al 2020), this difference may also have been due to possible problems in the cognitive system as an attention problem in the patient group.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, hearing loss and tinnitus characteristics (loudness and frequency) were indeed positively correlated with the psychoacoustic score of tinnitus, but their correlation was small, which also demonstrated its limitations in predicting psychoacoustic outcomes in tinnitus patients. The significantly higher frequency of tinnitus in the vanishing group than in the remission and unchanged groups may be explained by the fact that the daily auditory frequency in humans is predominantly low to medium frequencies, thus making it easier to benefit from transient neural suppression with sound therapy [ 30 ]. At the same time, when the ROC analysis was carried out, the results showed that the tinnitus frequency was helpful to the outcome of T-MIST.…”
Section: Discussionmentioning
confidence: 99%